Exploring factors influencing student study abroad choice of destination in the contemporary globalized era - Jamshed Khalid; Nordiana Mohd Nordin; Anees Janee Ali; Iftikhar, Umer; Jamil, Adnan (Penerbit Universiti Kebangsaan Malaysia, 2020)
The advent of global and international dimensions in higher education has lifted the trends of students’ and researcher’s mobility around the globe. Identification and assessment of international students’ drivers influencing their decision-making process of study destination are imperative to appeal to a larger number of international students. The present study aimed to examine the international students’ motives in the selection of Malaysia as a study destination and the factors influencing their will to recommend Malaysia to their friends and relatives. A qualitative approach was employed and a total of 18 respondents were interviewed. Quality of education and cultural adoption were found as thekey concerned fascination for international students in choosing Malaysia as a study destination. Besides, the low cost of living and tuition fees, cultural adoption, environmental beauty, credibility, and international ranking of institutions also appeal to students in the selection of Malaysia. The findings revealed that most of the respondents are willing to recommend Malaysia to their friends and relatives, and the factors prompting their intention are educational cost and quality, available research facilities at institutions, the credibility of Malaysian universities, and low tuition fee for higher education. The results would offer the current trends to thegovernment and higher education institutions in offering an exclusive experienceto the existing and potential students and in achieving Malaysia’s Vision-2025 of attracting 250,000 international students. The limitations and directions for future research have been provided.